2020
DOI: 10.1021/acsabm.0c01185
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Semiconducting Polymer Dots for Analytical Detection and NIR-II Fluorescence Imaging

Abstract: In recent years, semiconducting polymer dots (Pdots) have attracted enormous attention in applications from fundamental analytical detection to advanced deep-tissue bioimaging due to their ultrahigh fluorescence brightness with excellent photostability and minimal cytotoxicity. Pdots have therefore been widely adopted for a variety types of molecular sensing for analytical detection. More importantly, the recent development of Pdots for use in the optical window between 1000 and 1700 nm, popularly known as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 127 publications
0
27
0
Order By: Relevance
“…Detection of specific biomolecules in the human body is essential for clinical diagnosis, especially for the early diagnosis of numerous diseases. 87 Chen et al prepared a C 60 -PAMAM-PFO nanocomposite via the electrostatic adsorption action between PFO Pdots and C 60 -PAMAM (polyamidoamine). 88 Based on the fact that H 2 O 2 could enhance the ECL intensity of the PFO system, this C 60 -PAMAM-PFO nanocomposite was able to achieve the quantitative detection of H 2 O 2 .…”
Section: Applications Of Pdot-based Nano-sensors For In Vitro Detecti...mentioning
confidence: 99%
“…Detection of specific biomolecules in the human body is essential for clinical diagnosis, especially for the early diagnosis of numerous diseases. 87 Chen et al prepared a C 60 -PAMAM-PFO nanocomposite via the electrostatic adsorption action between PFO Pdots and C 60 -PAMAM (polyamidoamine). 88 Based on the fact that H 2 O 2 could enhance the ECL intensity of the PFO system, this C 60 -PAMAM-PFO nanocomposite was able to achieve the quantitative detection of H 2 O 2 .…”
Section: Applications Of Pdot-based Nano-sensors For In Vitro Detecti...mentioning
confidence: 99%
“…Wu et al found that Pdot-bioconjugates are much brighter (~30×) than QD-bioconjugates [ 71 ]. Additionally, Pdots also exhibit fast radiative rates and good photostability [ 72 , 73 ]. The PL mechanism of Pdots has been illustrated in the review by Zhu et al [ 57 ].…”
Section: Nanomaterial-based Ratiometric Fluorescent Biosensorsmentioning
confidence: 99%
“…Until now, different kinds of fluorescent nanomaterials have been developed such as carbon dots (CDs), [1][2][3][4] silicon nanoparticles (NPs), [5][6][7][8][9][10][11][12][13] semiconductor quantum dots (QDs), [14][15][16][17][18] polymer dots, [19][20][21] dye-doped NPs, [19,22] and upconversion NPs. [23,24] Among them, CDs are considered as suitable fluorescent bioprobes due to their properties like good biosafety, facile preparation and modification, fascinating photoluminescence (PL), and excellent aqueous dispersity.…”
Section: Introductionmentioning
confidence: 99%